PELAKSANAAN PELATIHAN CALON TENAGA KERJA BERBASIS PERMENAKERTRANS NO 8 TAHUN 2014 DI UPTPK PASURUAN - jurnalmap map; Fitria Handayani; Cathrine Sri Hartati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT The purpose of this study was to determine the description of the general description of the Pasuruan UPTPK; analyze the implementation of prospective labor force training based on Minister of Manpower and Transmigration Regulation No. 8 of 2014; what factors are supporting and inhibiting; what strategies are carried out in competency-based training for prospective workers. This research was conducted with a qualitative method approach. The technique of data collection is done by interview techniques (in-depth interviews). The results showed that the Pasuruan UPTPK was a work training institution under the Manpower and Transmigration Office of East Java Province; Competency-based training carried out in Planning, Implementation and Evaluation has been running well and in accordance with Minister of Manpower and Transmigration Regulation No. 8 of 2014 concerning Guidelines for Implementing Competency Based Training; supporting factors: strategic location, availability of sufficient training facilities, instructors who are competent in their field, availability of funds for training, training programs in accordance with SKKNI; inhibiting factors: lack of labor and funds to identify training needs, training programs are still national in nature, lack of practical facilities / infrastructure. The strategy undertaken is to assign instructors, conduct third party cooperation, submit funds to the center or region. Keywords: competency, competency-based training, workforce